Vaccination as a Solution for Improving the Community's Economy (Study on MSME Activities (Micro, Small, and Medium Enterprises) in Jenggawah Sub-District after Vaccination Activities) - Umbara, Bastomi Dani; Wijiyono, Slamet; Kusumawati, Astrian; Fawaid, Achmad (Proceeding of Saizu International Conference on Transdisciplinary Religious Studies, 2022)
Pandemic The COVID-19 that has occurred since early 2020 has had a tremendous impact on growtheconomyworld and national. According to the Minister of Finance, Sri Mulyani, last year's world economic growth had fallen sharply to minus 3.2 percent. This condition has caused many countries to experience a recession, including Indonesia. In this study, researchers used an intrinsic qualitative research approach. The use of this method is to find and understand what is hidden behind a phenomenon which is sometimes difficult to understand. While the results of this study are that the effectiveness of vaccination on the economic activities of the Jenggawah District community is very significant after the vaccination program is carried out as a whole. This can be seen from several aspects, one of which is the MSME activities, which are the main foundation of the community's economy, are running as they should. Apart from that, the activities of factory workers in Jenggawah Subdistrict have started to carry out their activities as they should after the vaccination program for factory workers was carried out. For this reason, the vaccination program for the Janggawah community has a very positive value in improving the economy during the Covid-19 pandemic.